2021
DOI: 10.3389/fcell.2021.686664
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Characterization of Novel Immune Gene Signatures Predicts Prognostic Factors in Hepatocellular Carcinoma

Abstract: Background: The prognosis of patients with hepatocellular carcinoma (HCC) is negatively affected by the lack of effective prognostic indicators. The change of tumor immune microenvironment promotes the development of HCC. This study explored new markers and predicted the prognosis of HCC patients by systematically analyzing immune characteristic genes.Methods: Immune-related genes were obtained, and the differentially expressed immune genes (DEIGs) between tumor and para-cancer samples were identified and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…Dendritic cells (DCs) are pivotal in orchestrating T-cell immune reactions, with the antigen presentation by resting DCs to CD8+ T cells potentially elevating tolerance (Probst, McCoy et al 2005, Ouyang, Wu et al 2016. Furthermore, metabolism stands as a cornerstone in the dynamic between immune and cancer cells within the tumor milieu, influencing both immune surveillance and evasion mechanisms (Xie, Bai et al 2020, Xu, Wang et al 2021. In sum, our research underscores NAM's paramount influence on the immune landscape of HCC.…”
Section: Discussionmentioning
confidence: 81%
“…Dendritic cells (DCs) are pivotal in orchestrating T-cell immune reactions, with the antigen presentation by resting DCs to CD8+ T cells potentially elevating tolerance (Probst, McCoy et al 2005, Ouyang, Wu et al 2016. Furthermore, metabolism stands as a cornerstone in the dynamic between immune and cancer cells within the tumor milieu, influencing both immune surveillance and evasion mechanisms (Xie, Bai et al 2020, Xu, Wang et al 2021. In sum, our research underscores NAM's paramount influence on the immune landscape of HCC.…”
Section: Discussionmentioning
confidence: 81%
“…The risk model exhibited a strong performance in survival prediction. Previous studies have identified that ATG10 was associated with autophagy, immune response, and tumor metastasis in HCC ( Zhang J. et al, 2021 ; Chen et al, 2021 ; Xu et al, 2021 ), which suggested that UPS-related genes might contribute to HCC development through regulating biological process. FBXL7, an F-box protein that binds to substrates via SKP1-Cullin-1-F-box (SCF) E3 ubiquitin ligase, could enhance polyubiquitylation and degradation of substrates in tumor occurrence and aggression ( Wang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 96%
“…Both SLC11A1 and SLC2A3 are members of the solute carrier family and are responsible for encoding membrane transport proteins 50,51 . Reportedly, SLC11A1 not only predicts the prognosis of colorectal cancer and hepatocellular carcinoma 52,53 but also serves as a stratification indicator for immunotherapy or chemotherapy in glioma patients 54 . SLC2A3 exerts multiple biological functions in different cancers, including tumor EMT, ferroptosis, glycolytic reprogramming, drug resistance and immunity 55–59 .…”
Section: Discussionmentioning
confidence: 99%